El principio de igualdad en materia laboral a partir de la Constitución de 1991. Análisis jurisprudencial - Cabrera Suárez, Lizandro Alfonso (2023)
The paper will examine the constitutional and legal rules on labor rights, as well as the development of the case law and the applicability of the principle of equality in labor relations in Colombia. It is vital to note that the core principles, including equality, are a guarantee for citizens who are part of a welfare state based on the rule of law, which is ba sed on the dignity of people; therefore, something that is vital for human beings, as is work, is protected.